'Try it with the Tip of a Knife': Looking Out for Fake Antiquities in Sixteenth-Century Italy. (2nd January 2022) - Furlotti, Barbara
Summary: In 1565, the collector and art adviser Girolamo Garimberto congratulated Cesare Gonzaga on the recent acquisition of a series of ancient heads. In Garimberto's words, what made this purchase so extraordinary was the "presence of an emperor [Geta] so rare, with his wife and two children, that, to tell the truth, this is an extremely rare and impossible occurrence, difficult to be arranged in any century, if not by sculpting them ex novo." While approving the acquisition, Garimberto was voicing a deep concern: collectors' high demand for "rare and impossible" works was encouraging the creation of forgeries. During the sixteenth century, for instance, the growing request for ancient coins with unusual reverses fostered a flourishing production of skilfully made fakes, which dealers were not ashamed to bring to the market that were still scorching hot. In such a competitive context, it was crucial to learn how to recognise an original coin from a fake, for instance by scratching the metal with the tip of a knife or hitting it to check its sound. As the market for antiquities boomed, so did the production of fake coins, sculptures, gems, inscriptions. This article highlights some of the problems scholars face when investigating the topic of fake antiquities produced in Italy during the early modern period. Through the discussion of some sixteenth-century forgeries, it also considers by whom and for whom fake antiquities were created, and what kind of expertise was required to identify them.